The Role Of Islamic Religious Education In Overcoming The Negative Influence Of Technology On Students SMK Muhammadiyah - Ellisa Fitri Tanjung; Rizka Harfiani (Proceeding International Seminar of Islamic Studies, 2019)
In its essence the progress of technologi and its influence in life are things that we cannot be avoided, because now we can know how advanced tehcnologi has affected lifestyle and mindset of the community especially students. Adolescence is aperiod of seaching for identity, and it could be in the proses of finding that identity the students goes the righ way or the wrong way. If student fail to developing a sense of identity, then students will lose direction. Religious teachers SMK Muhammadiyah trying to reduce the negative influence of technology thruogh learning Islamic education by sharpening morals learning and character, add hours to religious studies, creating and Islamic learning environment at school, and includ elements of moral education in all student activities. Research on the problems in this study is; (1) Describe the negative influence of technology on students (2) what is the role of Islamic religious education in overcoming the negative influence of technology? (3) can Islamic religious education overcome the negatif influence of technolgy on students SMK Muhammadiyah? This research uses descriptive qualitative methods, that is describing and explaining the symptoms or facts based on their real state. This research was conducted in SMK Muhammadiyah. Source data from class x, the subject of the study consisted of 25 students.